Legal Analysis of a Foundation's Legal Entity Status under Law Number 28 of 2004: Intersection of Social and Commercial Interests - Yunus, Nur Rohim; Aji, Ahmad Mukri; Mukri, Syarifah Gustiawati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to analyse the legal status of foundations by Law No. 28 of 2004 and to examine the legal implications of the misuse of foundation functions between social and business interests. Foundations, as non-profit legal entities, play a strategic role in social and educational activities; however, in practice, there is a potential for the misuse of their functions for business activities that conflict with their social goals. This study employs a qualitative method, combining a literature and legislative approach, which analyses various legal sources and related provisions to explore the legal regulations surrounding foundations, their role in social and business activities, and the legal implications of a foundation deviating from its social goals. The results of the study indicate that although Law No. 28 of 2004 provides a clear legal basis for foundations, the practice of misusing foundation functions for business activities can still occur. Therefore, strict government supervision and adherence to the principles of transparency and accountability are necessary to ensure that foundations continue to operate in accordance with the social goals mandated by law.Keywords: Foundation; legal entity; Law No. 28 of 2004; social activities; business activities; legal implications